Impact of COVID-19 on Mental Health of the Health Care Workers: A Cross sectional Study at Sher- E- Bangla Medical College Hospital, Barishal (American Journal of Medical Science and Innovation, 2023)
The world is passing through and is being challenged by the emergence of a novel Severe Acute Respiratory Syndrome Corona virus (SARS-Cov-2). The World Health Organization (WHO) proclaimed the 2019 Corona Virus Disease (COVID-19) an international public health emergency on January 30, 2020. (WHO). A structured questionnaire was used to conduct a cross-sectional study. The Patient Health Questionnaire (PHQ9) and Generalized Anxiety Disorder-7 (GAD-7) were used as the two instruments to assess the symptoms of anxiety and depression in HCWs. Inferential statistics like the independent t-test, one-way ANOVA, and Pearson Product Moment Correlation Coefficient were used to examine the relationship between general psychological impact and socio-demographic factors. Descriptive statistics like frequency, percentage, mean, and standard deviation were used to describe the socio-demographic characteristics. The age varied from 30-55 years, with a mean of 34.92 (SD=6.65). More than half (53.3%) of the respondents were Muslims, and the majority (84.8%) of them were female. The average GAD7 score was 2.65 (SD:.76). The findings showed that only 18.5 respondents had been diagnosed with severe depression, whereas 50% of respondents scored as having moderate levels of anxiety. The average GAD7 score was 2.65 (SD:.76). As mental health issues were strongly related to all the mental health outcomes, more than half of the health workers experienced depression and only a few reported generalized anxieties at work. More anxious than other healthcare professionals were nurses. By emphasizing these things, it is advised that health workers can improve their mental health.